PENGARUH MEDIA SOSIAL TIK TOK TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS V A MADRASAH IBTIDAIYAH NEGERI (MIN) 1 BULUKUMBA - Harpina, Harpina; Irfandi, M Aldi (STIT Ibnu Rusyd Tanah Grogot, 2022)
We often hear the word social media. Social media is one of the masterpieces of modern tools that can be used by various groups for certain purposes. Tik Tok is one of the many applications on social media that is also the most widely used, say by students.Tik Tok is an internet-based application that contains unique features for making videos and accompanied by a myriad of music from various types of music that exist in the world that can be selected as desired. This social media can make its users addicted, because the features in it can also view videos edited by other people. The purpose of this study was to determine how much influence is generated when being an active user of Tik Tok social media on the learning achievement of students in class VA MIN 1 Bulukumba. This study uses a qualitative research with a descriptive approach that uses a questionnaire/questionnaire and interviews. The results showed that there was a significant effect on the use of the applicationTik Tok. This is in accordance with data sourced from questionnaires/questionnaires and interviews that have been obtained from respondents plus supporting data for student learning achievement.